Sociomateriality Implications of Software As a Service Adoption on IT-Workers’ Roles and Changes in Organizational Routines of IT Systems Support - Mbuba, F; Wang, YYC; Olesen, K (Springer, 2015)
This paper aims to deepen our understanding on how sociomateriality practices influence IT workers’ roles and skill set requirements and changes to the organizational routines of IT systems support, when an organization migrates an on-premise IT system to a software as a service (SaaS) model. This conceptual paper is part of an ongoing study investigating organizations that migrated on-premise IT email systems to SaaS business models, such as Google Apps for Education (GAE) and Microsoft Office 365 systems, in New Zealand tertiary institutions. We present initial findings from interpretive case studies. The findings are, firstly, technological artifacts are entangled in sociomaterial practices, which change the way humans respond to the performative aspects of the organizational routines. Human and material agencies are interwoven in ways that reinforce or change existing routines. Secondly, materiality, virtual realm and spirit of the technology provide elementary levels at which human and material agencies entangle. Lastly, the elementary levels at which human and material entangle depends on the capabilities or skills set of an individual.
Keywords: Cloud computing; Sociomateriality; IT workers; Materiality; Organizational change; Organizational routines; On-premise IT system; Software as a service (SaaS)